Description of a Rare Case of Nodular Fasciitis of the Apical Aspect of the Upper Buccal Sulcus - Ana Amélia Souza; Eldon Guttenberg Cariri Neto; Vera Cavalcanti de Araújo; Fabricio Passador-Santos; Maria Teresa de Seixas Alves; Andresa Borges Soares (Hindawi Limited, 2016)
This report describes a rare case of nodular fasciitis (NF) of the oral cavity, discussing the clinical, histological, and immunohistochemical characteristics. Histopathologic diagnosis of this type of lesion can be challenging due to its differential diagnosis, which principally includes sarcoma. The patient presented with a painless, well-defined nodule, reported as increasing in size, located at the apical aspect of the upper left buccal sulcus. Histologically, the lesion revealed spindle cell proliferation arranged in fascicles, while immunohistochemistry demonstrated positivity for smooth muscle actin. Eight months after complete surgical excision, no signs of local recurrence have been observed.